Preparation of gastro-resistant pellets containing chitosan microspheres for improvement of oral didanosine bioavailability - Patrícia Severino; George G.G. de Oliveira; Humberto G. Ferraz; Eliana B. Souto; Maria H.A. Santana (Elsevier, 2012)
The purpose of this work was to introduce a new concept of coated pellets containing chitosan microspheres loaded with didadosine for oral administration, aiming at reducing the frequency of administration and improving the bioavailability by a suitable release profile. Chitosan microspheres were produced under fluidized bed, followed by extrusion and spheronization to obtain pellets with a mean diameter of about 1 mm. The pellets were then coated with Kollidon® VA64 and Kollicoat® MAE100P in water dispersion to depict a sustained release profile. Conventional hard gelatine capsules were loaded with these pellets and tested in vitro for their release profile of didadosine. Dissolution testing confirmed that chitosan microsphere pellets provides appropriate sustained release up to 2 h behavior for didanosine. Keywords: Didanosine, Pellets, Gastro-resistance, Coating, Microspheres, Chitosan